Arthroscopic Double-Row Suture Anchor Repair of Acute Posterior Bony Bankart Lesion - Ly, Justin A. (Arthrosc Tech, 2016)
The treatment of anterior shoulder instability is well described with various techniques, including arthroscopic double-row repair, an alternative to open stabilization procedures in high-risk groups. The surgical management of posterior instability in high-risk and athletic populations is a less-explored entity. We describe our technique for an all arthroscopic double-row suture anchor repair of a large posterior bony Bankart lesion. We prefer this technique over percutaneous cannulated screw fixation because the double-row suture technique allows for incorporation of capsular plication with bony fixation in an effort to better restore normal anatomy for capsulolabral complex. Double-row repair capsulolabral repair or fixation of the bony Bankart is performed via a suture-bridge technique. Medial row anchors are placed down the glenoid neck and shuttled around the bony fragment and labrum. The lateral-row anchor is placed at the rim of the native glenoid. This repair technique has been shown to increase the surface area for healing and more closely reconstruct the native anatomic capsulolabral complex footprint, improve force distribution, and potentially impart enhanced posterior stability to the glenohumeral joint.